2008
DOI: 10.1002/kin.20388
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the oxygen atom transfer reactions of peroxomonosulfate: Oxidation of glycolic acid

Abstract: The kinetics of oxidation of glycolic acid, an α-hydroxy acid, by peroxomonosulfate (PMS) was studied in the presence of Ni(II) and Cu(II) ions and in acidic pH range 4.05-5.89. The metal glycolate, not the glycolic acid (GLYCA), is oxidized by PMS. The rate is first order in [PMS] and metal ion concentrations. The oxidation of nickel glycolate is zero-order in [GLYCA] and inverse first order in [H + ]. The increase of [GLYCA] decreases the rate in copper glycolate, and the rate constants initially increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…It has been shown that the oxidation of glycolic acid by PMS in the presence of Ni(II) and Cu(II) proceeds through the formation of hydroperoxide intermediate 3. When the reactions are carried out in the presence of formaldehyde and [HCHO] > [Ni(II)], the rate is second order with respect to [PMS] and we observed the decomposition of PMS instead of the oxidation of nickel lactate 17.…”
Section: Resultsmentioning
confidence: 54%
See 1 more Smart Citation
“…It has been shown that the oxidation of glycolic acid by PMS in the presence of Ni(II) and Cu(II) proceeds through the formation of hydroperoxide intermediate 3. When the reactions are carried out in the presence of formaldehyde and [HCHO] > [Ni(II)], the rate is second order with respect to [PMS] and we observed the decomposition of PMS instead of the oxidation of nickel lactate 17.…”
Section: Resultsmentioning
confidence: 54%
“…Thus the importance has led to the extensive investigations on the kinetics and mechanism of oxidation of lactic acid. The oxidation of glycolic acid, another alpha hydroxy acid, by peroxomonosulfate (PMS) in the presence of metal ions such as Ni(II) and Cu(II) ions at pH 4.05–5.89 has been reported from this laboratory 3. The deprotonated form of PMS (SO 2−5) reacts with nickel glycolate to give nickel glycolate peroxomonosulfate intermediate, which rearranges to a hydroperoxide by the oxygen atom transfer to the hydroxyl group of the chelated glycolic acid.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier results from this laboratory 3 show that glycolic acid is stable with PMS and nickel glycolate is oxidized to oxalic acid/oxalate by PMS. The reaction between glycolic acid and PMS, in the presence of HCHO, initially proceed at a slow and measurable speed and when [PMS] consumed reaches approximately the concentration of HCHO the rate becomes very slow and this shows that in the absence of Ni(II) ions only formaldehyde is oxidized.…”
Section: Resultsmentioning
confidence: 83%
“…Peroxomonosulfate (PMS), HSO 5 is a two equivalent oxidant, and in a number of systems PMS reacts through oxygen atom transfer 2 from the terminal peroxide following nucleophilic attack (at the peroxide moiety) by the substrate. The oxidation of nickel glycolate by PMS in the acidic pH was studied in our laboratory 3. The results suggest that the probable mechanism may be the transfer of peroxide oxygen to the hydroxyl group, resulting in a hydroperoxide intermediate.…”
Section: Introductionmentioning
confidence: 99%
“…It is also proved to be a strong oxidizing agent compared to other traditional reagents like peroxodisulphate and peroxomonophosphoric acid [16][17][18][19][20][21]. The predominant reactive species of PMS in acidic medium is HSO À 5 and it is more reactive than SO 2À 5 .…”
mentioning
confidence: 95%